If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + -4x = 7 + -7xequation Solving 28 + -4x = 7 + -7aeinoqtux Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7aeinoqtux' to each side of the equation. 28 + 7aeinoqtux + -4x = 7 + -7aeinoqtux + 7aeinoqtux Combine like terms: -7aeinoqtux + 7aeinoqtux = 0 28 + 7aeinoqtux + -4x = 7 + 0 28 + 7aeinoqtux + -4x = 7 Add '-28' to each side of the equation. 28 + 7aeinoqtux + -28 + -4x = 7 + -28 Reorder the terms: 28 + -28 + 7aeinoqtux + -4x = 7 + -28 Combine like terms: 28 + -28 = 0 0 + 7aeinoqtux + -4x = 7 + -28 7aeinoqtux + -4x = 7 + -28 Combine like terms: 7 + -28 = -21 7aeinoqtux + -4x = -21 Reorder the terms: 21 + 7aeinoqtux + -4x = -21 + 21 Combine like terms: -21 + 21 = 0 21 + 7aeinoqtux + -4x = 0 The solution to this equation could not be determined.
| 130*0.3048-25t=15 | | 8(m+3)=48 | | 6c-9=36c+20 | | y=60000+1 | | 13x+10=69 | | 5u-8v+9(2u-3v)-4(2v-5u)= | | 3x^4+5x^3-x^2-5x-2=0 | | 130-25t=15 | | (4x-3)2+7=39 | | x*3+x*2-12=0 | | 5x^2+20x-30=15 | | 23x+6-27x=2-8 | | 5c+2=5c+4 | | z=10-2x^2 | | f(-5)=(x^2)-5x+7 | | Ax+3=6x+b | | 3x^2+2x+10=900 | | 4x-8=12(4+3x) | | -19(5c-8)-12c= | | (4x-12)(x+7)=0 | | p=140-0.5x | | -6=2x-1x | | 6x^2+22x-18=0 | | y=-a-x | | Ln(x)=24 | | 6x^2+22-18=0 | | 6a=6a+12 | | x(x-4)(x+14)=0 | | ax+1=bx-y | | P=80x-.4x^2-200 | | .8x-4=2x-3 | | 21x-5x=32 |